Resposta enzimática, fisiológica e produtiva do tomateiro e desempenho de porta enxertos resistentes à murcha bacteriana - Silva, Ewerton Gasparetto da [UNESP] (2015)
Bacterial wilt caused by Ralstonia solanacearum (Rs) is one of major disease on tomato. There is no market cultivars / commercial hybrids resistant to the pathogen. Rootstocks with resistance are used in order to control bacterial wilt (BW). The pathogen can survive in the soil for many years. Also, to influence gas exchange, in the activity of enzymes involved in defense mechanisms and productivity of the affected plants. The above, the objectives of the study were to evaluate the activity of the enzymes superoxide dismutase (SOD), catalase (CAT), peroxidase (POD), polyphenol oxidase (PPO) and phenylalanine ammonia lyase (PAL) as biochemical stress responses related to defense against bacterial wilt in tomato; evaluate the efficiency of grafting to control bacterial wilt; compare gas exchange of grafted and not grafted plants inoculated with BW and also check the productivity of these plants in plastic house with the pathogen. Three trial were conducted, two in a plastic house at the Faculty of Agricultural Sciences of Botucatu UNESP, and the third in a protected environment in Ituaú Farm in the Salto city. In the first trial, we evaluated the enzymatic activities (SOD, CAT, POD, PPO and PAL) in the leaves and stems of grafted and not grafted plants, inoculated with Rs in nine samples that were performed at 0, 12, 24, 48, 72, 96, 120, 144 and 288 hours after inoculation. In the second, we evaluated the incidence of bacterial wilt with 0, 5, 10, 15 and 20 days after inoculation (DAI) and gas exchange with 0, 3, 6, 9 and 12 DAI on grafted and not grafted plants inoculated with Rs . The third trial it was evaluated the incidence of bacterial wilt at 10, 20, 30, 40, 50, 60, 70 and 80 days after transplantat in grafted plants on three different rootstocks and non grafted plants at soil naturally infested with Rs. Based on the results were concluded: The enzymes SOD, CAT and PAL, to the leaves, and SOD, ...